The Power to Destroy - Roth, William V. 1921-2003.; Nixon, William (William Holladay) (New York : Atlantic Monthly Press, 1999)
The Power to Destroy tells the behind-the-scenes story of the congressional investigation of the IRS, the steps that have been taken to curb its abuses of power, and Senator Roth's proposals for far-reaching changes that still need to be made. Along the way, Roth and Nixon vividly re-create the stories of the victims of the Internal Revenue Service using exclusive interviews with those who have been unjustly audited, foreclosed, prosecuted, and worse.
With explosive new investigative material - including unreleased internal surveys from IRS employees across the nation - the authors show how corruption, mismanagement, perverse incentives, and negligence exist inside a culture that is as cloistered as it is powerful. The book concludes with an explanation of what you need to know about your rights under the new tax laws - and what to do if you are audited.
1. Anatomy of an Investigation -- 2. When Things Are Worse than You Expect -- 3. Collections -- 4. The IRS vs. Small Business -- 5. Management -- 6. Management's Impact on Taxpayers -- 7. When Taxpayers Are Innocent -- 8. Criminal Investigations -- 9. Congressional Accountability -- 10. Protect Yourself.
Includes bibliographical references (p. 273-282) and index.
Keywords: United States. -- Internal Revenue Service; Tax collection -- United States; Tax administration and procedure -- United States